Dessa gente que vai em frente : uma história visual sobre modernização e periferia em Porto Alegre (1975-1979) - Alvim, Alexandra Lis (2023)
The contact sheets filed in the Acervo Fotográfico Permanente da Coordenação de Comunicação Social do Gabinete do Prefeito comprise an extensive amount of images produced for institutional documentation and for the dissemination of the actions of the municipal administrations of Porto Alegre (RS, Brazil). They function as a visual immersion in the history of the city's metropolization. From 1975 onwards, in the first term of Guilherme Socias Villela, other bodies and landscapes began to occupy the images of the Gabinete do Prefeito: peripheral spaces and bodies, communities totally related to the processes of expulsion and modernization that occurred during the Brazil Civil-Military Dictatorship. In the visual history that the archived images of the Gabinete do Prefeito tell, why, between 1975 and 1979, did these communities receive greater attention from the municipal government? What factors explain the emergence of an insistent appearance of poorly paved communities and barefoot children in the files produced by the City Hall? This thesis tries to answer these answers based on a sample of contact sheets from Restinga, Vila Nova Brasília, Vila Mapa, Vila Batista Xavier and Vila São José and concludes that these images were part of the great battle over the city that was being built at the time - the mayor's presence in the communities can be considered both a symptom and a consequence of the popular communities' demand movement that emerged in Porto Alegre